2009
DOI: 10.1021/pr900212u
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Modifications of the Human Salivary Secretory Protein Complex

Abstract: Physiological variability of the naturally occurring, human salivary secretory peptidome was studied as a function of age. The qualitative and quantitative changes occurring in the secretion of proteins/peptides specific to the oral cavity (i.e., basic salivary proline-rich proteins, salivary acidic proline-rich phosphoproteins, statherin, proline-rich peptide P-B, salivary cystatins, and histatins) were investigated by high-performance liquid chromatography-electrospray ionization-mass spectrometry in 67 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 45 publications
5
63
1
2
Order By: Relevance
“…As previously shown, precipitation did not affect significantly the quali/quantitative profile of acid-soluble proteins (23). Levels of salivary proteins and naturally occurring peptides were determined by HPLC-ESI-MS analysis, and the typical chromatographic profile obtained under our experimental conditions in the two groups under study is shown in Figure 1.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…As previously shown, precipitation did not affect significantly the quali/quantitative profile of acid-soluble proteins (23). Levels of salivary proteins and naturally occurring peptides were determined by HPLC-ESI-MS analysis, and the typical chromatographic profile obtained under our experimental conditions in the two groups under study is shown in Figure 1.…”
Section: Resultssupporting
confidence: 53%
“…In a previous work devoted to the investigation of the influence of the age on salivary protein composition, we evidenced that the expression of basic PRPs is age-related and that these salivary proteins reach the concentration found in adults only after puberty (12-17 years of age) (23). Since the age of the subjects enrolled for this study was comprised between 7-18 years, basic PRPs (bPRPs) were not considered in the present investigation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous study (6), we have established that some salivary proteins and peptides reach the levels typically observed in the adult around 18 years of age. Encouraged by the noninvasive specimen collection, we explored the salivary protein composition of at-term and preterm newborns, in order to establish the starting point of the secretion of the proteins and peptides specific of saliva.…”
mentioning
confidence: 77%
“…This process leads to great variation in the peptide profile and thus limits the reproducibility of peptidomic analyses. Other preanalytical variables, such as sex, age, diet, and circadian rhythms, can also play important roles in the peptide composition of saliva (29 ). Despite these shortcomings, peptidomic analyses of saliva have been used to assess a variety of pathologies, including Sjögren syndrome, xerostomia, and diabetes (30 ).…”
Section: Peptidomics Of Salivamentioning
confidence: 99%